Incident investigation work-aid tool for process safety management compliance in process industries - Abdul Majid, N.D.; M. Shariff, A. (John Wiley and Sons Inc., 2020)
Incident investigations conducted in industries vary based on company policies and authorities' requirements. One of the related regulations as required by authorities is based on incident investigation elements of the process safety management (PSM) standard, 29 CFR 1910.119(m). This standard outlines the requirements for identification of catastrophic incident, incident investigation team setup, report writings, follow-up actions on the established recommendations, communication of incident investigation findings with relevant personnel, and report record keeping. Many companies implement that the incident investigations based on 29 CFR 1910.119(m) likely lead to noncompliance due to wrong interpretations of the requirements. This article presents a structured and easy technique to conduct and implement incident investigations that comply with Occupational Safety and Health Administration (OSHA) PSM 29 CFR 1910.119(m). A framework and a work-aid tool for incident investigation were developed and validated with a previous incident investigation of a catastrophic accident as a case study. The developed work-aid tool could benefit the process industries to track and manage incident investigation activities systematically. It also helps to prompt users on the necessary actions to close the identified gaps that caused the accident. This technique allows users to manage incident investigation better, to avoid recurrence of the same accident in future, and at the same time to reduce adverse impacts on people, environment, and assets. Â© 2019 American Institute of Chemical Engineers